Factors affecting farmers’ willingness to grow alternative biomass feedstocks for biofuels across Kansas - Caldas, Marcellus M.; Bergtold, Jason S.; Peterson, Jeffrey M.; Graves, Russell W.; Earnhart, Dietrich; Gong, Sheng; Lauer, Brian; Brown, J. Christopher (My University, 2014)
Energy conservation has emerged as one of the biggest challenges of the world in the XXI century, and not different from many countries, the US has created plans and policies to stimulate renewable energy alternative. Among the important alternatives for energy conservation is the use of biomass energy. Despite these stimuli production predictions are not confident that production would achieve the planned target for the U.S. Consequently, the predictions raise questions about farmer's willingness to grow bioenergy crops or produce alternative cellulosic feedstocks. In other words, farmers and landholders may not be willing to grow bioenergy crops. With this concerns in mind, the study advances previous research about bioenergy production by evaluating farmer's and landholder's willingness to produce different varieties of biofuel feedstocks. To achieve our goals, we used a mail survey of Kansas farmers conducted from January to April of 2011. The survey contained questions related to how farmers make their land-use decisions covering a wide array of topics. Through this survey, we evaluate the effect of farm characteristics, farm management practices, farmer perceptions (such as risk aversion), physical variables (such as soil, weather, and the availability of water for irrigation) on farmers' willingness to produce value-added feedstocks (e.g., corn stover), dedicated annual bioenergy crops (e.g., energy sorghum), and dedicated perennial bioenergy crops (e.g., switchgrass) for biofuel production in Kansas, though the use of logistic regressions and marginal effects.
Factors affecting farmers’ willingness to grow alternative biofuel feedstocks across Kansas
Keywords: Feedstocks; Biofuel; Farmer's willingness; Kansas; Crop choice; Scenarios